2018
DOI: 10.3389/fpls.2018.01333
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Headed Monster to Avert Disaster: HBS1/SKI7 Is Alternatively Spliced to Build Eukaryotic RNA Surveillance Complexes

Abstract: The cytosolic RNA exosome, a 3′→5′ exoribonuclease complex, contributes to mRNA degradation in eukaryotes, limiting the accumulation of poorly-translated, improperly translated, or aberrant mRNA species. Disruption of cytosolic RNA exosome activity allows aberrant RNA species to accumulate, which can then be detected by host antiviral immune systems as a signature of pathogen infection, activating antiviral defenses. SKI7 is a critical component of the cytosolic RNA exosome in yeast, bridging the catalytic exo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 66 publications
1
18
0
Order By: Relevance
“…This is consistent with published data from other eukaryotes (Kowalinski et al, 2016;Kalisiak et al, 2016;Marshall et al, 2018). The zebrafish ski7specific exon (exon 5) contains the previously annotated Ski7-like motif and the most conserved region of Ski7, the so-called patch 4-like (P4) motif (Kowalinski et al, 2016;Brunkard & Baker, 2018) (Fig. 1C).…”
Section: Ski7 Mrna Is Highly Expressed During the Oocyte-to-embryo Trsupporting
confidence: 91%
See 3 more Smart Citations
“…This is consistent with published data from other eukaryotes (Kowalinski et al, 2016;Kalisiak et al, 2016;Marshall et al, 2018). The zebrafish ski7specific exon (exon 5) contains the previously annotated Ski7-like motif and the most conserved region of Ski7, the so-called patch 4-like (P4) motif (Kowalinski et al, 2016;Brunkard & Baker, 2018) (Fig. 1C).…”
Section: Ski7 Mrna Is Highly Expressed During the Oocyte-to-embryo Trsupporting
confidence: 91%
“…In this study, we provide the first functional characterization of vertebrate Ski7 and the consequences of its absence. Zebrafish Ski7, similar to its human and plant homologs (Kalisiak et al, 2016;Kowalinski et al, 2016;Brunkard & Baker, 2018), is encoded as an alternative splice isoform of hbs1l. We found that zebrafish ski7 but not hbs1l mRNA is highly expressed in mature eggs and early embryos, which prompted us to investigate Ski7's role during the oocyte-to-embryo transition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In yeast, the genes encoding Ski7 and Hbs1, which binds to Dom34 (PELOTA in humans and plants) for the release of stalled ribosomes 35 , arose from a whole genome duplication event. In other eukaryotes including mammals and plants, the SKI7 and HBS1 proteins are produced by alternative splicing from a single locus 3638 .…”
mentioning
confidence: 99%